Issues and Challenges of Adoption of IFRS for SMEs in Malaysia - Vicky Vendy; Diarany Sucahyati (Future Science, 2021)
The purpose of this research is to look into issues and challenges associated with the adoption of International Financial Reporting Standards for Small and Medium Enterprises (IFRS for SMEs) or so-called MPERS (Malaysian Private Entity Reporting System). Using keywords like